The productive service employee: personality, stress, satisfaction and performance. Issue 6 (12th October 2017) - Harris, Eric G.; Fleming, David E.
Abstract : Purpose: The purpose of this study is to more closely examine the trait antecedents and outcomes of frontline employee productivity propensity. The study is the first to use a job demands-resources perspective on productivity propensity and it reveals that the inclusion of the construct into service worker personality studies significantly improves the explanatory ability of hypothesized models. Design/methodology/approach: The study follows a job demands-resources perspective and uses an empirical study that included two subsamples: banking and health care. Path analyses were performed using two-group modeling to test the hypotheses. Mediation and hierarchical regressions were also used. Findings: The findings indicate that the conscientiousness trait has a consistent effect on productivity propensity. More importantly, the findings reveal that productivity propensity influences role ambiguity, job satisfaction and self-rated service performance and that the addition of the construct into personality studies significantly improves the explanatory ability of personality models. Research limitations/implications: This study presents further evidence that productivity propensity is an important construct in services research. Beyond previously established influences on bottom-line service productivity and manager-rated work performance, the current work indicates that it also influences FLE stress, engagement and work outcomes. Practical implications: Managers work under pressures to ensure service productivity and are well aware of the importance of selecting job applicants who will fit the service role. This study provides additional evidence that the productivity propensity work resource should be considered when selecting employees. The work also suggests that customer workload and the standardization of the service environment impacts the influence of productivity propensity on service outcomes. Social implications: Given the importance of transformative service experiences that uplift the experiences of consumers and employees, the productivity propensity of frontline service employees not only impacts the ability of the employee to satisfy customer needs, but also leads the employee to experience increased job satisfaction. Originality/value: This work is the first work to consider the effects of productivity propensity from a job demands-resources perspective and, as such, the first to examine the influence of the construct on job satisfaction and service delivery.